Super nozzle cleaner for ceiling fan blade - Nursyahira, Omar (2018)
Ceiling fan is considered the most effective for most types of fans, as they effectively distribute air in the room to make drafts throughout the room. Most of South East Asia especially in Malaysia, ceiling fans will be installed even though some houses use air conditioning as their cooling system. Ceiling type fans are extensively used in dwellings, offices and many other types of buildings to circulate air and thereby reduce the cost of heating during cold weather and air-conditioning during hot weather. Thus, the suitable cleaning tools are needed to clean the ceiling fan blades efficiently. There are three problems faced when cleaning the ceiling fan which are position issues which the consumers need to use ladder to clean the ceiling fan blade especially on the upper part of the blade. Furthermore, consumers faced problems in time consuming and inappropriate design of cleaning tool which most of the dust will falling down to the floor during cleaning activities and due to that, the users need to clean the floor after clean the ceiling fan blades. Solution to the problems, a new design of vacuum nozzle is proposed. From the result obtained, the wind speed and room temperature are increase and decrease respectively after cleaning by the super nozzle vacuum. Based on the result of super nozzle testing, cleaning ceiling fan blades only took less than one minute. The results also show by using super nozzle vacuum cleaner, people will have no difficulty to clean their ceiling fan blades.